Aplikasi E-Marketplace untuk Kelompok Usaha Himpunan Nelayan Seluruh Indonesia (HNSI) Kecamatan Palang, Kabupaten Tuban - Yoppy Yunhasnawa (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2019)
Each day, fishermen and people living in Palang Subdistrict, Tuban Regency are able to harvest and produce various kinds of fish and processed marine products. Most of the people and fishermen usually are only able to sell their seafood to collectors or middlemen. This is because the community and fishermen do not have the capacity to market their products extensively outside the region so that the benefits they get are not maximized. Therefore, it is necessary to innovate and develop a web-based marketplace system that aims to facilitate the people and fishermen under the auspices of the Indonesian Fishermen Association of Palang District to sell their marine products without having to go through middlemen. In this study, an E-Marketplace platform is designed to be able to meet these goals.